THU0278 ADVERSE PREGNANCY OUTCOMES (APOS) AFTER MULTI-PROFESSIONAL FOLLOW-UP IN WOMEN AFFECTED BY SYSTEMIC LUPUS ERYTHEMATOSUS (SLE). REPORT FROM A SINGLE CENTER IN SOUTHERN SWEDEN. (June 2019) - Saleh, Muna; Jonsen, Andreas; Bengtsson, Anders; Compagno, Michele
Abstract : Background: Systemic lupus erythematosus (SLE) often affects women in childbearing age. Modern management of SLE patients has improved the pregnancy outcomes over the last years. However, there is still an increased risk of maternal, fetal and neonatal complications (1). Objectives: We report our experience in the multi-professional follow-up of pregnant women affected by SLE. Our aim was to investigate the association of potential risk factors with the occurrence of adverse pregnancy outcomes (APOs). Methods: We selected the patients who have had one or more pregnancies, between January 2002 and January 2018, among all the SLE patients at the Department of Rheumatology, University Hospital in Lund, Sweden. Longitudinal clinical and laboratory data from rheumatology and obstetrics units, as well as from neonatal units, were collected and analyzed. We assessed the association between APOs and putative SLE-related risk factors as well as known risk factors in the selected population. Results: We investigated the outcome of 59 pregnancies in 28 SLE patients. Eighteen (64.3%) patients had one or more APOs. Forty-four (74.6%) pregnancies terminated with a delivery, whereof 36 (61%) term pregnancies and 8 (13.6%) before 36 gestational weeks. Caesarean section terminated 13 (29.5%) pregnancies. Thirteen (22%) miscarriages and two (3.4%) intentional abortions were recorded. HELLP syndrome occurred in 1 (1.7%) and pre-eclampsia in 11 (18.6%) gestations. Among 16 cases of fetal growth restriction, 5 (8.5%) gestations resulted in intrauterine growth restriction, 1 (1.7%) in a small for gestational age baby and 10 (24.4%) in low birth weight. No cases of eclampsia, stillbirths or congenital heart disease were recorded. Neonatal lupus erythematosus occurred in 1 (1.7%) baby. APOs were associated with anti-phospholipid syndrome and/or presence of anti-phospholipid antibodies (OR 4.5 - p = 0.009). Previous renal involvement was associated with APOs (OR 5.9 - p = 0.005) and with fetal growth restriction (OR 11 - p =0.03). Active disease (SLEDAI >3) six months before or during pregnancies was associated with miscarriage (OR 13 - p =0.02). Pre-eclampsia and pre-term deliveries were not significantly associated with any of the investigated risk factors. Conclusion: One or more APOs occurred in the majority of patients in our study and a few severe outcomes were recorded. Our experience suggests that the presumptive risk factors for APOs in SLE patients are disease related, such as high disease activity six months before or during pregnancies, previous renal involvement and anti-phospholipid syndrome/antibodies. Reference: 1IM Jakobsen, RB Helmig & K Stengaard-Pedersen (2015) Maternal and foetal outcomes in pregnant systemic lupus erythematosus patients: an incident cohort from a stable referral population followed during 1990-2010, Scandinavian Journal of Rheumatology, 44:5, 377-384, DOI: 10.3109/03009742.2015.1013982 Disclosure of Interests: None declared